Kontribusi dan Peran KH. Hasyim Asy’ari dalam Membingkai Moderasi Beragama Berlandaskan al Quran dan Hadis di Indonesia - Farida, Umma (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This article aims to reveal the ideas of Kiai Hasyim Asy'ari in knitting the unity and framing the religious moderation based on the Quran and Hadith in Indonesia. His role is still relevant to study considering the life of Indonesian people until now still often confront and even contradict between religion and culture. Besides, the dichotomy between traditionalist and modernist Islam has strengthened once again in the internal circles of Muslims, which if it was not immediately found a solution, it can lead to divisions between them. This study uses qualitative methods and data collection uses documentation techniques to be analyzed descriptively-critically. This research shows that Kiai Hasyim Asy'ari played a significant role in uniting Muslims in particular and Indonesian society in general. He taught Islam by emphasizing the formation of character, politeness, gentleness, and moderate understanding of Islam as stated in his book Risalah Ahl as-Sunnah wa al-Jama'ah. He also called for doing good to others despite being of different religions, loving the Prophet, and making unity, brotherhood, and tolerance as the foundation of moderation between religious communities in Indonesia.